2013
DOI: 10.1186/1471-244x-13-190
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of quality of life in methadone treatment patients in northern Taiwan: a follow-up study

Abstract: BackgroundThis study examined long-term improvement of quality of life amongst heroin users enrolled in methadone maintenance treatment (MMT).MethodsThe sample contained 553 heroin-dependent individuals from 4 hospitals in northern Taiwan who enrolled in MMT for an average of 184 days. Each patient signed a consent form and was assessed prospectively 3 times semi-annually. Quality of life was measured using the WHOQOL-BREF questionnaire, 26 items of which were scored by the participants. The WHOQOL-BREF consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 24 publications
7
40
7
1
Order By: Relevance
“…MMT improved significantly the quality of life of MMT outpatients (1,9,16,19,27,28). In this study quality of life scores were shown to have improved in direct proportion to the MMT duration; nevertheless.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…MMT improved significantly the quality of life of MMT outpatients (1,9,16,19,27,28). In this study quality of life scores were shown to have improved in direct proportion to the MMT duration; nevertheless.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies demonstrated that MMT continually improved outpatients' mental health. 1,9,27,30 Also employment, marriage, health (affected by an underlying chronic disease) and education are the most important factors that may affect DASS subscales scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decades of experience have demonstrated that methadone maintenance treatment (MMT) is currently the most effective intervention measure for controlling opioid use and its related HIV transmission among opioid users (4)(5)(6). Meanwhile, MMT could improve stability for society (7) and help drug users recover their physical and social functions (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%